Legal Effectiveness of Halal Product Certification in Improving Business Economics in Indonesia and Malaysia - Supriyadi, Supriyadi; Aulia, Rahma; Nubahai, Labib; Rahman, Rozanah Ab; Mohamed, Rosmah (Al-Ahkam, 2024)
Law Number 33 of 2014 and Government Regulation Number 31 of 2019 in Indonesia shifted halal certification from voluntary to mandatory on October 17, 2019, contrasting with Malaysia's voluntary system under the 2011 Akta Perihal Dagang (APD). This study aims to scrutinize the legal regulations of halal certification in both countries and assess their impacts on business entities. Employing a qualitative method with a phenomenological approach reveals differences in certification procedures, notably in application-to-issuance stages. Indonesia provides a self-declaration mechanism for micro and small businesses, while Malaysia lacks such a provision. Nonetheless, material inspection principles align in both nations. Most respondents perceive halal certification as crucial for sales turnover, despite challenges posed by the COVID-19 pandemic. This research is significant for businesses and governments on how to manage halal certification in both countries.